PELESTARIAN ENSAMBEL TALEMPONG GANDANG LASUANG MELALUI PENGEMBANGAN INSTRUMENTASI, MUSIKAL DAN ASPEK PERTUNJUKANNYA - Susandra Jaya; Yurnalis Yurnalis; Hajizar Hajizar; Indriyetti Indriyetti (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT The presentation of the traditional musical ensemble Talempong Gandang Lasuang has its own uniqueness and characteristics that have been able to represent the character and tradition of its supporting community in the village of Padang Kunik, Sikapak, Pariaman, West Sumatra. This music is very functional, formerly as a means of entertainment for women who cook in the kitchen at the wedding ceremony. But now this traditional music loses its function, because it has been abandoned by the current generation. In this condition, the purpose of innovating and developing are to produce the packaging of the composition of Talempong Gandang Lasuang musical in a form of innovation that is expected to influence the taste of art for young generation without eliminating their traditional values. one approach used by making a new musical compositions based on research as a qualitative formulation with several artists and their supporting communities. In addition to innovating musical compositions, the aesthetics of the show are arranged as well as possible, and present the dance performances that are truly arranged to the maximum level, so that the Talempong Gandang Lasuang performance is not only in the form of musical performances, but also presents dance compositions to accom-pany the songs played on Talempong Gandang Lasuang.